Proapoptotic Bcl-2 inhibitor as potential host directed therapy for pulmonary tuberculosis - Medha Singh; Mona O. Sarhan; Nerketa N. L. Damiba; Alok K. Singh; Andres Villabona-Rueda; Oscar J. Nino-Meza; Xueyi Chen; Yuderleys Masias-Leon; Carlos E. Ruiz-Gonzalez; Alvaro A. Ordonez; Franco R. D’Alessio; Eric O. Aboagye; et al. (Nature Communications)
Abstract Mycobacterium tuberculosis establishes within host cells by inducing anti-apoptotic Bcl-2 family proteins, triggering necrosis, inflammation, and fibrosis. Here, we demonstrate that navitoclax, an orally bioavailable, small-molecule Bcl-2 inhibitor, significantly improves pulmonary tuberculosis (TB) treatments as a host-directed therapy. Addition of navitoclax to standard TB treatments at human equipotent dosing in mouse models of TB, inhibits Bcl-2 expression, leading to improved bacterial clearance, reduced tissue necrosis, fibrosis and decreased extrapulmonary bacterial dissemination. Using immunohistochemistry and flow cytometry, we show that navitoclax induces apoptosis in several immune cells, including CD68+ and CD11b+ cells. Finally, positron emission tomography (PET) in live animals using clinically translatable biomarkers for apoptosis (18F-ICMT-11) and fibrosis (18F-FAPI-74), demonstrates that navitoclax significantly increases apoptosis and reduces fibrosis in pulmonary tissues, which are confirmed in postmortem analysis. Our studies suggest that proapoptotic drugs such as navitoclax can potentially improve pulmonary TB treatments, reduce lung damage / fibrosis and may be protective against post-TB lung disease.